Reactions to Tristia Ex Melitogaudo: A Response - Fiorini, Stanley; Vella, Horatio C. R. (Literatūra, 2017)
This paper considers a number of reactions to and reviews of the editio princeps of a long poem recently published with the title Tristia ex Melitogaudo: Lament in Greek Verse of a XIIth-century Exile on Gozo. The editors clarify a number of points and answer objections raised by various authors.
Keywords: Malta; Normans; Arabs; Byzantine; Christianity; Exile